Fabrication and properties of a supramolecular hybrid hydrogel doped with CdTe quantum dots1. Issue 72 (6th August 2015) - Xie, Xi; Ma, Dong; Zhang, Li-Ming
<x xml:space="preserve">Abstract</x> A fluorescent supramolecular hydrogel was fabricated based on the host–guest self-assembly between the amphiphilic block copolymer on the CdTe quantum dot (QD) surface and the cyclic oligosaccharide host molecule, α-cyclodextrin (α-CD).